Sodium ferric phosphate pyrophosphate, preparation method, positive pole piece and sodium ion battery

Preparation of sodium ferric pyrophosphate by solid phase method solves the problems of complexity of existing methods and impurities, and achieves efficient and simple preparation process and excellent electrochemical properties.

CN119683594APending Publication Date: 2025-03-25ZHEJIANG NARADA POWER SOURCE CO LTD +1

Patent Information

Application Number
CN202411856977.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing preparation methods of sodium ferric pyrophosphate positive electrode materials are complex and are prone to produce sodium ferric phosphate impurities, which affects its electrochemical performance and stability.

Method used

Sodium ferric pyrophosphate was prepared by solid phase method. By mixing the phosphorus source, iron source, sodium source and carbon source in a specific molar ratio, adding dispersant and organic solvent, ball milling, vacuum drying and sintering, a pure phase sodium ferric pyrophosphate was obtained.

Benefits of technology

The preparation steps are simplified, the generation of impurities is avoided, the purity and electrochemical properties of the material are improved, and the positive electrode material of sodium ion battery with high capacity and excellent cycle stability is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683594A_ABST
    Figure CN119683594A_ABST
Patent Text Reader

Abstract

The invention discloses ferric sodium pyrophosphate, a preparation method, a positive pole piece and a sodium ion battery, and belongs to the technical field of secondary batteries. The preparation method comprises the following steps: S1, mixing a phosphorus element, an iron element, a sodium element and a carbon element in a phosphorus source, an iron source, a sodium source and a carbon source according to a molar ratio of (1-5): (1-3): (1-5): (0.1-0.5); adding a dispersing agent and an organic solvent; s2, carrying out ball milling on the mixture obtained in the step S1; s3, carrying out vacuum drying on the mixture subjected to ball milling; and S4, sintering the material treated in the step S3 to obtain the ferric sodium pyrophosphate. The preparation method of the ferric sodium pyrophosphate comprises the following steps: uniformly mixing a phosphorus source, an iron source, a sodium source and a carbon source through ball milling, and sintering to obtain the ferric sodium pyrophosphate. The ferric sodium pyrophosphate is prepared by adopting a solid phase method, the preparation steps are simple, and large-scale production is easier.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of secondary battery positive electrode materials, and in particular to sodium iron pyrophosphate, a preparation method, a positive electrode sheet and a sodium ion battery. Background Art

[0002] Secondary batteries, also known as rechargeable batteries, are batteries that can store and release electrical energy through electrochemical reactions and can be recharged and used multiple times through an external power source. Unlike primary batteries, which cannot be recharged after use, secondary batteries can be charged and discharged repeatedly within a certain number of times. Secondary batteries store and release electrical energy through electrochemical reactions and can be charged and discharged repeatedly within a certain number of times, with multiple advantages such as economy, environmental protection and flexibility. They are widely used in many fields such as portable electronic devices, transportation, energy storage systems, etc., and are an important support for modern science and technology and socio-economic development. With the continuous advancement of new materials and technologies, rechargeable batteries will continue to play a greater role in more fields, helping to build a cleaner, more efficient and sustainable future.

[0003] As two important types of secondary battery technology, lithium-ion batteries and sodium-ion batteries each play a key role in different application scenarios with their unique performance characteristics. Lithium-ion batteries dominate mobile devices, transportation vehicles and high-performance demand scenarios due to their high energy density and long cycle life; sodium-ion batteries, due to their low cost, abundant resources and good safety, show great potential in fixed energy storage systems, low-temperature environment applications, safety and stability demand scenarios, and low-cost demand scenarios. Sodium-ion batteries have shown great potential in the field of energy storage due to their advantages such as abundant resources, high safety, wide operating voltage range, long cycle life, strong environmental adaptability, mature manufacturing process and diverse application scenarios. Although its energy density may be slightly lower than that of lithium-ion batteries at present, sodium-ion batteries, as a sustainable energy storage technology, are expected to be more widely used and developed in the future under the background of limited resources and increasingly stringent environmental protection requirements.

[0004] Sodium iron pyrophosphate has a three-dimensional network structure, which is conducive to the embedding and extraction of sodium ions. At the same time, the stable structure gives it excellent cycle stability and life. As a potential positive electrode material for sodium-ion batteries, sodium iron pyrophosphate has shown great potential in fixed energy storage systems, low-temperature environment applications, and low-cost demand scenarios due to its abundant resources, low cost, stable structure, and good safety. Although it is still facing challenges in conductivity and energy density, with the deepening of research and technological advancement, sodium iron pyrophosphate is expected to become an important part of the field of sodium-ion batteries in the future, promoting clean energy technology and sustainable development.

[0005] Patent document CN117819507A discloses a method for preparing a spherical sodium iron pyrophosphate positive electrode material, wherein a sodium source, an iron source, a phosphorus source and a solvent are mixed, a primary particle precursor is obtained by hydrothermal reaction, and then the precursor is spray-dried after mixing with a carbon source to obtain a spherical precursor, and finally sintered in an inert atmosphere to obtain spherical sodium iron pyrophosphate. The disclosed preparation method requires hydrothermal reaction, spray drying, and high-temperature sintering, and the preparation steps are complicated. Summary of the invention

[0006] The object of the present invention is to provide a method for preparing sodium ferric pyrophosphate by a solid phase method with simple preparation steps; another object of the present invention is to provide a sodium ferric pyrophosphate prepared by a solid phase method; another object of the present invention is to provide a positive electrode sheet with sodium ferric pyrophosphate as an active material; another object of the present invention is to provide a sodium ion battery with sodium ferric pyrophosphate as an active material.

[0007] The present invention discloses a method for preparing sodium ferric phosphate pyrophosphate, comprising the following steps:

[0008] S1: mixing the phosphorus, iron, sodium and carbon elements in the phosphorus source, iron source, sodium source and carbon source in a molar ratio of 1-5:1-3:1-5:0.1-0.5; and then adding a dispersant and an organic solvent;

[0009] S2: ball milling the mixture obtained in step S1;

[0010] S3: vacuum drying the ball-milled mixture;

[0011] S4: Sintering the material processed in step S3 to obtain sodium iron pyrophosphate.

[0012] The dispersant can form a thin film on the surface of fine particles of the material during the sintering process. With continuous heating, the thin film will gradually decompose into a gas membrane, inhibiting the agglomeration of material particles and playing a dispersing role.

[0013] Furthermore, in step S1, the dispersant is selected from one or at least two of polyacrylamide, polyvinyl alcohol, polyethyleneimine, sodium polyacrylate, sodium carboxymethyl cellulose, and polyvinyl pyrrolidone; and the added mass of the dispersant is 1 / 3-1 / 2 of the mass of the carbon source.

[0014] The organic solvent functions as a physical dispersing solvent to uniformly mix the phosphorus source, iron source, sodium source and carbon source during ball milling.

[0015] Furthermore, in step S1, the organic solvent is selected from one or at least two of anhydrous ethanol, methanol, acetone, dichloromethane, ethyl acetate, and N-methylpyrrolidone; the added mass of the organic solvent is 1-1.5 times the sum of the masses of the phosphorus source, the iron source, the sodium source, and the carbon source.

[0016] In step S3, the temperature of vacuum drying is controlled at 80-100° C. The purpose of vacuum drying is to remove the organic solvent in the material.

[0017] Furthermore, in step S1, the phosphorus source is selected from one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium pyrophosphate, sodium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, acetyl phosphate, and pyrophosphate; the iron source is one or more of ferric phosphate, ferrous oxalate, ferric oxide, ferric carbonate, ferric hydroxide, ferric nitrate, ferric chloride, and ferrous sulfate; the sodium source is one or more of sodium carbonate, sodium pyrophosphate, sodium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, sodium citrate, sodium hydroxide, sodium nitrate, sodium chloride, and sodium sulfate; and the carbon source is one or more of glucose, citric acid, sucrose, starch, ascorbic acid, graphite, and carbon black.

[0018] Furthermore, in the step S2, the rotation speed of the ball milling treatment is 300-400 r / s, and the ball milling time is 3-8 h.

[0019] The phosphorus source, iron source, sodium salt and carbon source are mixed in the form of tiny particles by ball milling, so that the mixing is more uniform.

[0020] Furthermore, in the step S4, the sintering operation is: heating to 400-600° C. in a protective gas atmosphere, and the sintering time is 7-15 hours.

[0021] Furthermore, in step S1, the phosphorus source is selected from one or both of diammonium phosphate and sodium pyrophosphate; the iron source is ferrous oxalate; the sodium source is selected from one of sodium pyrophosphate or sodium carbonate; in step S4, the sintering is: in a protective gas atmosphere, the temperature is raised to 500° C., and the sintering treatment time is 9-11 hours.

[0022] Sodium iron phosphate may produce sodium iron phosphate impurities during its synthesis, which will affect its electrochemical performance and stability as a positive electrode active material. By limiting the phosphorus source, iron source, and sodium source to the above ranges and controlling the sintering temperature at 500°C, sodium iron phosphate pyrophosphate free of sodium iron phosphate impurities will be prepared, and the assembled sodium ion battery has a discharge capacity of more than 100 mAh / g and excellent cycle performance.

[0023] The invention also discloses sodium ferric phosphate pyrophosphate, which is prepared by the preparation method as described above.

[0024] The present invention also discloses a positive electrode sheet, comprising a positive electrode current collector, the sodium iron phosphate pyrophosphate as described above, a binder, and a conductive agent.

[0025] The material of the positive electrode current collector can be selected from that used in conventional sodium ion batteries, preferably aluminum foil with a thickness of 8-16 μm.

[0026] The materials coated on the outer surface of the positive electrode current collector are measured by mass percentage, and the positive electrode material active substance sodium ferric phosphate pyrophosphate is 60-90%, the binder is 5-20%, and the conductive agent is 5-20%.

[0027] The binder and the conductive agent may be those used in conventional positive electrode materials for sodium ion batteries.

[0028] The present invention also discloses a sodium ion battery, comprising the positive electrode plate, the separator, the electrolyte, and the negative electrode plate as described above.

[0029] The material of the diaphragm is selected from one or more of glass fiber, polypropylene, polyethylene, and polyethylene terephthalate.

[0030] The electrolyte comprises sodium salt, an organic solvent and an additive.

[0031] The sodium salt includes one or more of sodium perchlorate, sodium hexafluoroarsenate, sodium tetrafluoroborate, sodium hexafluorophosphate, sodium trifluoromethylsulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide.

[0032] The organic solvent includes one or more of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, diethanol dimethyl ether, and diethylene glycol dimethyl ether.

[0033] The additive includes one or more of vinylene carbonate, fluoroethylene carbonate, trans-difluoroethylene carbonate, vinyl sulfite, 1,3-propane sultone, succinonitrile, propenyl-1,3-sultone, vinyl sulfate, and dimethyl methylphosphonate.

[0034] The negative electrode plate can be selected from conventional sodium-ion batteries, preferably sodium plates.

[0035] The invention provides a method for preparing sodium ferric phosphate pyrophosphate, which comprises the following steps: uniformly mixing a phosphorus source, an iron source, a sodium source and a carbon source by ball milling, and then obtaining the sodium ferric phosphate pyrophosphate by sintering; and obtaining the sodium ferric phosphate pyrophosphate by a solid phase method, which has simple preparation steps and is easier to mass produce. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 is the XRD diffraction pattern of the sodium iron phosphate pyrophosphate powder prepared in Examples 1-9 of the present invention;

[0037] Figure 2 is a SEM image of the sodium iron pyrophosphate powder prepared in Example 4 of the present invention;

[0038] Figure 3 is a SEM image of the sodium iron pyrophosphate powder prepared in Example 9 of the present invention;

[0039] Figure 4 It is the charge and discharge curve of the sodium ion battery assembled with the sodium iron phosphate pyrophosphate prepared in Example 4 and Example 5 of the present invention;

[0040] Figure 5 This is the charge cycle curve of the sodium ion battery assembled with the sodium iron phosphate pyrophosphate prepared in Example 4 of the present invention. DETAILED DESCRIPTION

[0041] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0042] Example 1

[0043] Preparation of sodium ferric pyrophosphate:

[0044] NaH2PO4, Fe(NO)3 and glucose were added to the ball mill of the ball mill in sequence at a Na / Fe / P / C molar ratio of 4:2.85:4:0.3. In addition, polyethylene glycol (molecular weight 3000) with a mass of 1 / 2 of glucose and anhydrous ethanol with the same mass as the total material were added.

[0045] The speed of the ball mill was adjusted to 350 r / s and ball milling was performed for 8 h.

[0046] The ball-milled powder was dried in vacuum at 90°C to remove anhydrous ethanol.

[0047] The vacuum-dried powder was ground evenly with a mortar, placed in a tube furnace, and sintered at 550° C. for 10 h in a nitrogen atmosphere to obtain sodium iron pyrophosphate.

[0048] Example 2

[0049] Preparation of sodium ferric pyrophosphate:

[0050] Na2CO3, FePO4, NH4H2PO4 and glucose were added to the ball mill of the ball mill in sequence at a Na / Fe / P / C molar ratio of 4:2.85:4:0.3. In addition, polyethylene glycol (molecular weight 3000) with a mass of 1 / 2 of the glucose was added, and anhydrous ethanol with the same mass as the total material was added.

[0051] The speed of the ball mill was adjusted to 350 r / s and ball milling was performed for 8 h.

[0052] The ball-milled powder was dried in vacuum at 90°C to remove anhydrous ethanol.

[0053] The vacuum-dried powder was ground evenly with a mortar, placed in a tube furnace, and sintered at 550° C. for 10 h in a nitrogen atmosphere to obtain sodium iron pyrophosphate.

[0054] Example 3

[0055] Preparation of sodium ferric pyrophosphate:

[0056] Na4P2O7, FeC2O4, NH4H2PO4 and glucose were added to the ball mill of the ball mill in sequence at a Na / Fe / P / C molar ratio of 4:2.85:4:0.3. In addition, polyethylene glycol (molecular weight 3000) with a mass of 1 / 2 of the mass of glucose and anhydrous ethanol with the same mass as the total material were added.

[0057] The speed of the ball mill was adjusted to 350 r / s and ball milling was performed for 8 h.

[0058] The ball-milled powder was dried in vacuum at 90°C to remove anhydrous ethanol.

[0059] The vacuum-dried powder was ground evenly with a mortar, placed in a tube furnace, and sintered at 550° C. for 10 h in a nitrogen atmosphere to obtain sodium iron pyrophosphate.

[0060] Example 4

[0061] Preparation of sodium ferric pyrophosphate:

[0062] Na4P2O7, FeC2O4, NH4H2PO4 and glucose were added to the ball mill of the ball mill in sequence at a Na / Fe / P / C molar ratio of 4:2.85:4:0.3. In addition, polyethylene glycol (molecular weight 3000) with a mass of 1 / 2 of the mass of glucose and anhydrous ethanol with the same mass as the total material were added.

[0063] The speed of the ball mill was adjusted to 350 r / s and ball milling was performed for 8 h.

[0064] The ball-milled powder was dried in vacuum at 90°C to remove anhydrous ethanol.

[0065] The vacuum-dried powder was evenly ground with a mortar, placed in a tube furnace, and sintered at 500° C. for 10 h in a nitrogen atmosphere to obtain sodium iron pyrophosphate.

[0066] like Figure 2 As shown, the sodium iron pyrophosphate prepared in Example 4 is in the form of irregular spherical small particles.

[0067] Example 5

[0068] Preparation of sodium ferric pyrophosphate:

[0069] Na4P2O7, FePO4, FeC2O4, NH4H2PO4 and glucose were added to the ball mill jar of the ball mill in sequence at a Na / Fe / P / C molar ratio of 4:2.85:4:0.3. In addition, polyethylene glycol (molecular weight 3000) with a mass of 1 / 2 of the mass of glucose and anhydrous ethanol with the same mass as the total material were added.

[0070] The speed of the ball mill was adjusted to 350 r / s and ball milling was performed for 8 h.

[0071] The ball-milled powder was dried in vacuum at 90°C to remove anhydrous ethanol.

[0072] The vacuum-dried powder was evenly ground with a mortar, placed in a tube furnace, and sintered at 500° C. for 10 h in a nitrogen atmosphere to obtain sodium iron pyrophosphate.

[0073] Example 6

[0074] Preparation of sodium ferric pyrophosphate:

[0075] Na4P2O7, FePO4, FeC2O4, NaH2PO4 and glucose were added to the ball mill jar of the ball mill in sequence at a Na / Fe / P / C molar ratio of 4:2.85:4:0.3. In addition, polyethylene glycol (molecular weight 3000) with a mass of 1 / 2 of the mass of glucose and anhydrous ethanol with the same mass as the total material were added.

[0076] The speed of the ball mill was adjusted to 350 r / s and ball milling was performed for 8 h.

[0077] The ball-milled powder was dried in vacuum at 90°C to remove anhydrous ethanol.

[0078] The vacuum-dried powder was evenly ground with a mortar, placed in a tube furnace, and sintered at 500° C. for 10 h in a nitrogen atmosphere to obtain sodium iron pyrophosphate.

[0079] Example 7

[0080] Preparation of sodium ferric pyrophosphate:

[0081] Na2CO3, FePO4, FeC2O4, NaH2PO4 and glucose were added to the ball mill jar of the ball mill in sequence at a Na / Fe / P / C molar ratio of 4:2.85:4:0.3. In addition, polyethylene glycol (molecular weight 3000) with a mass of 1 / 2 of the glucose was added, and anhydrous ethanol with the same mass as the total material was added.

[0082] The speed of the ball mill was adjusted to 350 r / s and ball milling was performed for 8 h.

[0083] The ball-milled powder was dried in vacuum at 90°C to remove anhydrous ethanol.

[0084] The vacuum-dried powder was evenly ground with a mortar, placed in a tube furnace, and sintered at 500° C. for 10 h in a nitrogen atmosphere to obtain sodium iron pyrophosphate.

[0085] Example 8

[0086] Preparation of sodium ferric pyrophosphate:

[0087] Na2CO3, FeC2O4, NaH2PO4 and glucose were added to the ball mill jar of the ball mill in sequence at a Na / Fe / P / C molar ratio of 4:2.85:4:0.3. In addition, polyethylene glycol (molecular weight 3000) with a mass of 1 / 2 of the glucose was added, and anhydrous ethanol with the same mass as the total material was added.

[0088] The speed of the ball mill was adjusted to 350 r / s and ball milling was performed for 8 h.

[0089] The ball-milled powder was dried in vacuum at 90°C to remove anhydrous ethanol.

[0090] The vacuum-dried powder was evenly ground with a mortar, placed in a tube furnace, and sintered at 500° C. for 10 h in a nitrogen atmosphere to obtain sodium iron pyrophosphate.

[0091] Example 9

[0092] Preparation of sodium ferric pyrophosphate:

[0093] Na2CO3, FeC2O4, NH4H2PO4 and glucose were added to the ball mill jar of the ball mill in sequence at a Na / Fe / P / C molar ratio of 4:2.85:4:0.3. In addition, polyethylene glycol (molecular weight 3000) with a mass of 1 / 2 of the glucose was added, and anhydrous ethanol with the same mass as the total material was added.

[0094] The speed of the ball mill was adjusted to 350 r / s and ball milling was performed for 8 h.

[0095] The ball-milled powder was dried in vacuum at 90°C to remove anhydrous ethanol.

[0096] The vacuum-dried powder was evenly ground with a mortar, placed in a tube furnace, and sintered at 500° C. for 10 h in a nitrogen atmosphere to obtain sodium iron pyrophosphate.

[0097] like Figure 3As shown, the sodium iron pyrophosphate prepared in Example 9 is in the form of irregular spherical small particles.

[0098] The sodium iron phosphate pyrophosphate prepared in Example 1-9 was subjected to an X-ray powder diffraction test, and the obtained XRD diffraction pattern is as follows: Figure 1 As shown, from Figure 1 It can be seen that the diffraction characteristic peaks of the impurity sodium iron phosphate appear in Examples 1-3, 5-8, while the diffraction characteristic peaks of sodium iron phosphate do not appear in Examples 4 and 9. Therefore, the sodium iron pyrophosphate prepared in Examples 4 and 9 is pure phase.

[0099] Preparation of positive electrode

[0100] The sodium iron phosphate pyrophosphate prepared in Example 1-9, the conductive agent carbon black, and the binder polyvinylidene fluoride are added to a stirring tank in a mass ratio of 8:1:1 and mixed. During stirring, 3 times the mass of the material (sodium iron phosphate pyrophosphate, conductive agent and binder) of the solvent N-methylpyrrolidone (NMP) is added. After the mixture is stirred evenly, a positive electrode slurry is obtained. The positive electrode slurry is coated on the current collector aluminum foil with a coating thickness of 200 μm. The mixture is dried at 80°C for 24 hours, and the dried electrode membrane is cut into circular electrode sheets with a diameter of 12 mm to obtain the positive electrode sheets of the sodium iron phosphate pyrophosphate battery.

[0101] Assembling a sodium-ion battery

[0102] Electrolyte: Sodium salt is 1 mol / L NaPF6, solvent is ethylene carbonate and ethyl methyl carbonate (volume ratio 1:1), additive is 1% fluoroethylene carbonate of the total mass of the electrolyte.

[0103] The material of the diaphragm is glass fiber with a thickness of 25μm.

[0104] The negative electrode is a sodium plate.

[0105] The sodium ion positive electrode sheet, negative electrode sheet, and glass fiber material separator prepared in Examples 1-9 are assembled into button batteries.

[0106] Performance Testing

[0107] The button cells assembled from Examples 1-9 were tested for charge-discharge performance and cycle performance. The test conditions for charge-discharge performance were room temperature test environment, test voltage of 2-4V, and charge-discharge current density of 0.1C. The test conditions for cycle performance were room temperature test environment, test voltage of 2-4V, and charge-discharge current density of 0.5C. The test results are shown in Table 1. Figure 4-5 And as shown in Table 1.

[0108] Table 1 Performance test results of button cells composed of Examples 1-9

[0109]

[0110] like Figure 4-5 As shown in Table 1, compared with other embodiments, the button-type batteries assembled from pure-phase sodium iron phosphate pyrophosphate prepared in Examples 4 and 9 have a discharge capacity greater than 100 mAh / g, and a capacity retention rate greater than 99% after 200 cycles. This shows that pure-phase sodium iron phosphate pyrophosphate is more conducive to material capacity and has better cycle stability.

[0111] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing sodium ferric pyrophosphate, characterized in that: The following steps are involved: S1: mixing the phosphorus, iron, sodium and carbon elements in the phosphorus source, iron source, sodium source and carbon source in a molar ratio of 1-5:1-3:1-5:0.1-0.5; and then adding a dispersant and an organic solvent; S2: ball milling the mixture obtained in step S1; S3: vacuum drying the ball-milled mixture; S4: Sintering the material processed in step S3 to obtain sodium iron pyrophosphate.

2. The method for preparing sodium ferric phosphate pyrophosphate according to claim 1, characterized in that: In the step S1, the dispersant is selected from one or at least two of polyacrylamide, polyvinyl alcohol, polyethyleneimine, sodium polyacrylate, sodium carboxymethyl cellulose, and polyvinyl pyrrolidone; and the added mass of the dispersant is 1 / 3-1 / 2 of the mass of the carbon source.

3. The method for preparing sodium ferric phosphate pyrophosphate according to claim 2, characterized in that: In step S1, the organic solvent is selected from one or at least two of ethanol, methanol, acetone, dichloromethane, ethyl acetate, and N-methylpyrrolidone; the added mass of the organic solvent is 1-1.5 times the sum of the masses of the phosphorus source, the iron source, the sodium source, and the carbon source.

4. The method for preparing sodium ferric phosphate pyrophosphate according to claim 1, characterized in that: In the step S1, the phosphorus source is selected from one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium pyrophosphate, sodium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, acetyl phosphate, and pyrophosphate; the iron source is one or more of ferric phosphate, ferrous oxalate, ferric oxide, ferric carbonate, ferric hydroxide, ferric nitrate, ferric chloride, and ferrous sulfate; the sodium source is one or more of sodium carbonate, sodium pyrophosphate, sodium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, sodium citrate, sodium hydroxide, sodium nitrate, sodium chloride, and sodium sulfate; and the carbon source is one or more of glucose, citric acid, sucrose, starch, ascorbic acid, graphite, and carbon black.

5. The method for preparing sodium ferric phosphate pyrophosphate according to claim 1, characterized in that: In the step S2, the rotation speed of the ball milling treatment is 300-400 r / s, and the ball milling time is 3-8 h.

6. The method for preparing sodium ferric phosphate pyrophosphate according to claim 1, characterized in that: In the step S4, the sintering operation is: heating to 400-600° C. in a protective gas atmosphere, and the sintering time is 7-15 hours.

7. The method for preparing sodium ferric phosphate pyrophosphate according to claim 1, characterized in that: In the step S1, the phosphorus source is selected from one or both of diammonium phosphate and sodium pyrophosphate; the iron source is ferrous oxalate; the sodium source is selected from one of sodium pyrophosphate and sodium carbonate; in the step S4, the sintering is: in a protective gas atmosphere, the temperature is raised to 500° C., and the sintering treatment time is 9-11 hours.

8. A sodium ferric pyrophosphate, characterized in that The method is prepared according to any one of claims 1 to 7.

9. A positive electrode sheet, characterized in that: The method comprises a positive electrode current collector, the sodium iron phosphate pyrophosphate as claimed in claim 8, a binder and a conductive agent.

10. A sodium ion battery, characterized in that: It comprises the positive electrode plate, the separator, the electrolyte and the negative electrode plate as described in claim 9.

Citation Information

Patent Citations

  • Preparation method of spherical ferric sodium pyrophosphate positive electrode material

    CN117819507A

Cited By

  • Method for producing ferric sodium pyrophosphate and extracting lithium from lithium iron phosphate black powder through replacement

    CN120172383A

  • Modified ferric sodium pyrophosphate positive electrode material as well as preparation method and application thereof

    CN120964755A

  • Sodium ion battery monomer, battery device and electric equipment

    CN121583996A